2007
DOI: 10.1517/14740338.6.5.547
|View full text |Cite
|
Sign up to set email alerts
|

Increased propensity for calcium phosphate kidney stones with topiramate use

Abstract: Topiramate (TPM) is a neuromodulatory agent that was initially approved as an antiepileptic drug and is increasingly used in the treatment of a number of neurological and metabolic disorders. Among its various pharmacological actions, TPM has been shown to inhibit the activity of specific carbonic anhydrase enzymes in the kidney. This action is associated with the development of metabolic acidosis, hypocitraturia, hypercalciuria and elevated urine pH, leading to an increased risk of kidney stone disease. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 93 publications
0
36
1
Order By: Relevance
“…Alkaline urine (pH Ͼ6.0) increases crystal precipitation within tubular lumens from drugs such as indinavir, oral sodium phosphate solution, and ciprofloxacin (23)(24)(25). In addition, drugs such as topiramate, zonisamide, and acetazolamide alkalinize the urine through inhibition of carbonic anhydrase and promote precipitation of calcium phosphate within tubules, thereby enhancing renal stone formation (26,27). The underlying genetic makeup of the host can also enhance renal vulnerability to potential nephrotoxins (28 -30).…”
Section: Risk Factors For Nephrotoxicitymentioning
confidence: 99%
“…Alkaline urine (pH Ͼ6.0) increases crystal precipitation within tubular lumens from drugs such as indinavir, oral sodium phosphate solution, and ciprofloxacin (23)(24)(25). In addition, drugs such as topiramate, zonisamide, and acetazolamide alkalinize the urine through inhibition of carbonic anhydrase and promote precipitation of calcium phosphate within tubules, thereby enhancing renal stone formation (26,27). The underlying genetic makeup of the host can also enhance renal vulnerability to potential nephrotoxins (28 -30).…”
Section: Risk Factors For Nephrotoxicitymentioning
confidence: 99%
“…Using this method, we found that the mean concentrations of (free) calcium ions in group I and group II calculi were 0.24 mmol/L and 0.35 mmol/L, respectively. The percentages of total phosphorus at the given pH, calculated from the dissociation constants of phosphoric acid [13] and reported as 4 ions, were 31% and 4.6% in groups I and II calculi, respectively. Using the procedure described previously [14], we calculated that the supersaturation of urine with respect to carbonate hydroxyapatite was 6.0 for group I (the solubility product of hydroxyapatite containing 2.2 wt% carbonate was 1.17 × 10 −57 mol 9 /L 9 [15]) and 23.6 for group II (the solubility product of stoichiometric hydroxyapatite was 2.03 × 10 −59 mol 9 /L 9 [13]).…”
Section: Thermal Analysismentioning
confidence: 99%
“…All stones containing calcium phosphate form in urine at higher pH [3][4][5][6]. In addition, hypercalciuria and hyperphosphaturia are often associated with phosphate stones [4,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, chronic metabolic acidosis may reduce growth rates. While the rate of kidney stones is estimated to be approximately 0.5 % in the general population, with some geographical variations, users of zonisamide and topiramate are found to have 1-4 % risk of developing nephrolithiasis, with men at greater risk than women (Vega et al, 2007). As with the effects of enzyme-inducing AEDs on the lipid profile, more studies are needed to elucidate more fully the clinical consequences of the drugs' effects on gonadal steroids.…”
Section: Potential Consequences Of the Metabolically Adverse Effects mentioning
confidence: 99%